Assessment of Emergency Medical Education on Knowledge Alterations of Medical Students in Rasoul Akram Hospital (2005-2006) - B Mahshidfar; N Kianmehr; M Mofidi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2007)
Background and objectives: Education and management are considered two integrated and non-separable requirements of an emergency department (ED). Despite the emphasis on teaching of essentials of approaching and management of critical patients, medical students do not acquire the necessary knowledge to handle these patients during their rotation in different specialties other than emergency medicine (EM). This study aims to evaluate the changes in EM knowledge of interns during their one month rotation in ED of Rasoul Akram Hospital. Methods: In a 15-month period, 226 interns were entered into this study. A pretest was taken at the beginning of their one-month internship period. Then, the interns were provided with a handbook, which was prepared and revised according to the approved curriculum of Ministry of Health and Medical Education of Iran and latest emergency medicine textbooks. The interns were taught by several lecture and practical sessions. At the end of their EM internship period, a post-test was taken and the change of their emergency medical knowledge was assessed by comparison of pre-and post-test results. Results: The results showed a significant increase of mean post-test scores compared with the pretest scores. Also, there was a significant difference between the scores obtained by males and those obtained by females (P < 0.001). Conclusion: The one-month EM training significantly improved the level of interns’ knowledge.